1999
DOI: 10.1016/s0092-8674(00)80760-6
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian Telomeres End in a Large Duplex Loop

Abstract: Mammalian telomeres contain a duplex array of telomeric repeats bound to the telomeric repeat-binding factors TRF1 and TRF2. Inhibition of TRF2 results in immediate deprotection of chromosome ends, manifested by loss of the telomeric 3' overhang, activation of p53, and end-to-end chromosome fusions. Electron microscopy reported here demonstrated that TRF2 can remodel linear telomeric DNA into large duplex loops (t loops) in vitro. Electron microscopy analysis of psoralen cross-linked telomeric DNA purified fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

39
1,793
3
20

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 2,180 publications
(1,855 citation statements)
references
References 48 publications
39
1,793
3
20
Order By: Relevance
“…The formation of G-quadruplex structures has been proposed as the Telomestatin dissociates TRF2 from telomeres H Tahara et al molecular mechanism that affords 3 0 overhang protection (Han and Hurley, 2000). Griffith and de Lange have demonstrated using electron microscopy that TRF2 proteins can remodel telomeric DNA into large duplex loop (t-loop) in vitro (Griffith et al, 1999), and various models of t-loop formation involving G-quadruplex DNA have been proposed (Han and Hurley, 2000). For example, the 3 0 overhang can fold over to form an intramolecular G-quadruplex (Williamson et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of G-quadruplex structures has been proposed as the Telomestatin dissociates TRF2 from telomeres H Tahara et al molecular mechanism that affords 3 0 overhang protection (Han and Hurley, 2000). Griffith and de Lange have demonstrated using electron microscopy that TRF2 proteins can remodel telomeric DNA into large duplex loop (t-loop) in vitro (Griffith et al, 1999), and various models of t-loop formation involving G-quadruplex DNA have been proposed (Han and Hurley, 2000). For example, the 3 0 overhang can fold over to form an intramolecular G-quadruplex (Williamson et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, expression of a dominant-negative mutant allele of TRF2, TRF2 DBDM , in human cells results in loss of the 3 0 overhang of telomeres, chromosome end-to-end fusions, and activation of the ATM/p53 DNA damage response pathway (Karlseder et al, 1999). An electron microscopy study has shown that TRF2 itself has the ability to remodel telomeric DNA into a 't-loop' (Stansel et al, 2001), in which the single-stranded guanine-rich terminus invades the duplex region of the telomere (Griffith et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The most terminal, single-stranded region of telomeres loop back and pair with an internal double-stranded location forming a stable loop structure -the telomeric cap (Griffith et al, 1999). Cells with telomeres in their capped state exhibit enhanced proliferative capacity, whereas the uncapped form coincides with cell cycle arrest (Blasco, 2007b).…”
Section: Msc Telomere and Telomerasementioning
confidence: 99%
“…Human telomeres consist of double stranded tandem repeats of the hexanucleotide sequence TTAGGG except for the terminal 3 0 G-rich overhang (Makarov et al, 1997;Wright et al, 1997). Telomeres can fold into t-loops that may result from the invasion of the 3 0 overhang into duplex DNA (Griffith et al, 1999) or into G-quadruplex (G4) DNA, an unusual DNA conformation based on guanine quartets (Oganesian and Bryan, 2007). Mammalian telomeres are associated with telomeric proteins or shelterin, forming a complex that functions to protect the ends of DNA from degradation and fusion, thus playing an essential role in controlling genomic stability (de Lange, 2005).…”
Section: Introductionmentioning
confidence: 99%